Induction of Labor in Post Dated Pregnancy with Intra-cervical Foley Catheter in Antenatal Ward - Dixit, Baburam; Manandhar, Tara; Sitaula, Sarita; Basnet, Tulasa (Birat Journal of Health Sciences, 2018)
Introduction: Induction of labor is one of the commonest obstetric procedures done these days with the aim of normal vaginal delivery. Among the different methods, transcervical Foley catheter is one of them used with great success and less complications. Objective: This study assesses the effect of intra-cervical Foley catheter in induction of labor in post dated pregnancy. Methodology: This was a descriptive observational study. Patients admitted in antenatal ward of BP Koirala Institute of Health Sciences (BPKIHS) with period of gestation (POG) ≥ 41 weeks without any complications were taken. Patients were induced either with Foley catheter or directly with misoprostol. Patients induced with Foley catheter were included in the study. Sixteen French Gauge Foley catheter was inserted intracervically and bulb was inflated with 40- 60 ml of distilled water and observed for 24 hours. If patient didn't go into labor after 24 hours with or without Foley expulsion, patient was reassessed and prostaglandin was used for further induction. Structured Pro forma was used for data collection and collected data was analyzed using SPSS software 11.5. Results: During the study period 353 patients were induced with intracervical Foley catheter. Among them 97(27.48%) went to labor and 256 (72.52%) needed further prostaglandin. Among 97 patients who went to labor 80 had normal vaginal delivery, 16 underwent cesarean section and one patient had vacuum assisted vaginal delivery. There were nine patients who had delivered baby with meconium stained liquor. Four patients had postpartum hemorrhage and two patients had intrapartum fever. None of the patients had hyper stimulation syndrome but one patient had still birth. Conclusion: Intracervical Foley catheter is one of the options to induce the patient in postdatism for priming the cervix to increase the rate of normal vaginal delivery with less complications. BJHS 2018;3(1)5 : 338-341